The Modeling of Multicriteria Assessment Activity in Enterprise Management - LÑƒudmyla Muhailyvna Malyarets; Vitalina Olekciivna Babenko; Oleksandr Volodumurovich Nazarenko; Nataliy Ivanivna Ryzhikova (International Journal of Supply Chain Management, 2019)
A lot of functions of enterprise management are grounded on the analytical basis that include the models of activity assessment which appears to be multicriteria under the complicated conditions of globalistics. The aim of the study is to improve the mathematical instrument for modeling the multicriteria assessment of enterprise activity. Taking into account the positive practice of using the Balanced Scorecard for assessing enterprise performance, its criteria are structured according to four components and serve for content assessment model. The assessment of enterprise activity based on the Balanced Scorecard mostly accounted for cause and effect interconnections, but this is just its level that influences the assessment. The paper presents the improved function of transforming the assessment criteria values and the formula of value calibration. The advantages of this function are flexibility and taking account the regular tendencies of changes in the criteria values. The level of enterprise performance is determined by an integrated index obtained as partial desirability functions folding by gmean. This generalizing desirability function is sensitive to small transformed criteria values that realizes tough requirements to assessment. The developed methodological approach in the modeling of multicriteria assessment of enterprise activity provides for taking into account the main criteria and possibility of their hierarchical systematization. The results of such modeling can be used in the processes of control, controlling and monitoring of this activity.